Usual interstitial pneumonia in ANCA-associated vasculitis: A poor prognostic factor - Maillet, Thibault; Goletto, Tiphaine; Beltramo, Guillaume; Dupuy, Henry; Jouneau, Stéphane; Borie, Raphael; Crestani, Bruno; Cottin, Vincent; Blockmans, Daniel; Lazaro, Estibaliz; Naccache, Jean-Marc; Pugnet, Grégory; et al. (Journal of autoimmunity, 2020)
Progressive fibrosing interstitial lung disease (ILD) is rarely associated with antineutrophil cytoplasm antibody (ANCA)-associated vasculitis (AAV). This study focused on the outcomes of ILD patients with associated AAV (AAV–ILD). AAV–ILD (cases: microscopic polyangiitis (MPA) or granulomatosis with polyangiitis (GPA) with ILD) were compared to AAV patients without ILD (controls). ILD was defined as a usual interstitial pneumonia (UIP) or non-specific interstitial pneumonia (NSIP) pattern. Two controls were matched to each case for age (>or ≤65 years), ANCA status (PR3-or MPO-positive) and creatininemia (≥or <150 μmol/L). Sixty-two cases (89% MPO-ANCA+) were included. Median age at AAV diagnosis was 66 years. ILD (63% UIP), was diagnosed before (52%) or simultaneously (39%) with AAV. Cases versus 124 controls less frequently had systemic vasculitis symptoms. One-, 3- and 5-year overall survival rates, respectively, were: 96.7%, 80% and 66% for cases versus 93.5%, 89.6% and 83.8% for controls (p = 0.008). Multivariate analyses retained age >65 years (hazard ratio (HR) 4.54; p < 0.001), alveolar haemorrhage (HR 2.25; p = 0.019) and UIP (HR 2.73; p = 0.002), but not immunosuppressant use, as factors independently associated with shorter survival. For AAV–ILD patients, only UIP was associated with poorer prognosis. Immunosuppressants did not improve the AAV–ILD prognosis. But in analogy to idiopathic pulmonary fibrosis, anti-fibrosing agents might be useful and should be assessed in AAV–ILD patients with a UIP pattern. •Progressive fibrosing interstitial lung disease is a rare comorbidity of MPO-vasculitis.•This condition is associated with shorter survival when it has a CT-scan UIP pattern.•Immunosuppressants did not improve the prognosis of these patients.•Our results support the evaluation of anti-fibrotic drugs in this condition.